Detecting pasteurella multocida causing pasteurellosis in Phan Rang sheep with PCR method - Nguyễn, Thị Kim Cúc; Nguyễn, Hữu Thọ; Nguyễn, Thị Diễm; Nguyễn, Thị Oanh; Hồ, Thị Xuân Túy; Bùi, Văn Lợi; Nguyễn, Xuân Huy; Lê, Công Tuấn; Nguyễn, Văn Phú (Hue University Journal of Science: Natural Science, 2023)
Pasteurellosis is an infectious disease causing severe damage to livestock and poultry since it leads to animals’ death, including sheep of all ages. In this study, we developed a sensitive, specific and accurate PCR method for detecting P. multocida in Phan Rang sheep using FKMT1/RKMT1 primers targeted to the KMT1 gene of P. multocida. The PCR-based method was used to detect the KMT1 gene from 104 copies of the KMT1-bearing plasmid. The method’s specificity was demonstrated by the successful amplification of KMT1 from the mixture containing other DNA of Gram-negative bacteria, such as E. coli or M. haemolytica. In particular, with the present method, we successfully detected P. multocida with crude DNA obtained from P. multocida or nasal swabs of pasteurellosis-suspected sheep samples treated in a TE buffer containing 0.1% TritonX-100. This is the first report on using a PCR-based method for detecting P. multocida from Phan Rang sheep, and it can serve as the basis for an effective procedure to diagnose pasteurellosis in sheep.